The Peritoneum: Beyond the Tissue – A Review - Isaza-Restrepo, Andres; Martin-Saavedra, Juan S.; Velez-Leal, Juan L.; Vargas-Barato, Felipe; Riveros-Dueñas, Rafael (Frontiers in Physiology, 2018)
Background: Despite its complexity, the peritoneum is usually underestimated in classical medical texts simply as the surrounding tissue (serous membrane) of the gut. Novel findings on physiology and morphology of the peritoneum and mesothelial cell exist but they are usually focused or limited to Continuous Ambulatory Peritoneal Dialysis research and practice. This review aims to expose, describe and analyze the most recent evidence on the peritoneum’s morphology, embryology and physiology. Materials and Methods: A literature review was performed on Pubmed and MEDLINE. With no limit of publication date, original papers and literature reviews about the peritoneum, the peritoneal cavity, peritoneal fluid, and mesothelial cells were included (n = 72). Results: Peritoneum develops in close relationship to the gut from an early period in embryogenesis. Analyzing together the development of the primitive gut and the surrounding mesothelium helps understanding that the peritoneal cavity, the mesenteries and other structures can be considered parts of the peritoneum. However, some authors consider that structures like the mesenteries are different to the peritoneum. The mesothelial cell has a complex ultrastructural organization with intercellular junctions and apical microvilli. This complexity is further proven by the large array of functions like selective fluid and cell transport; physiological protective barrier; immune induction, modulation, and inhibition; tissue repair and scarring; preventing adhesion and tumoral dissemination; cellular migration; and the epithelial-mesenchymal transition capacity. Conclusion: Recent evidence on the anatomy, histology, and physiology of the peritoneum, shows that this structure is more complex than a simple serous membrane. These results call for a new conceptualization of peritoneum, and highlight the need of adequate research for identifying clinical relevance of this knowledge.